Avalanche leds based on nanostructured silicon for optical interconnections - Le Dinh Vi; A. A. Leshok; A. V. Dolbik; S. L. Perko; S. K. Lazarouk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The paper analyzes the parameters of silicon avalanche LEDs and their use for electron-optical signal transmission systems. The advantages of silicon avalanche LEDs are shown, among which high speed and compatibility with silicon technology should be highlighted. Experimental avalanche LEDs based on nanostructured silicon were fabricated and studied. The results of controlling the electroluminescence spectrum of avalanche LEDs due to the choice of production conditions to form nanostructured silicon are presented. It was found that the temperature of the substrate during the deposition of the surface nanocomposite aluminum + silicon film affected the size of the formed silicon nanoparticles determining the spectral characteristics of avalanche LEDs. This allows shifting the maximum of their emission spectrum to a shorter wavelength region of the visible range due to the forming of smaller silicon nanoparticles. The authors have developed an optical interconnection system consisting of avalanche LEDs based on nanostructured silicon and a microchannel silicon wafer used to transmit a light signal. The study of various operating modes of the developed optoelectronic system was performed and an increase in the efficiency of optocouple based on avalanche LEDs to 0.2% due to the pulsed operating mode was achieved. It is shown that the efficiency of the optocouple increases with LED current and it is the pulsed mode of its operation that is characterized by the maximum current, which is due to more efficient removal of Joule heat in the intervals between pulses, ensuring stable operation of the entire system. The results obtained open up new opportunities for the development of optical interconnections between silicon chips and silicon optoelectronics in general.